2017
DOI: 10.3847/1538-3881/153/2/54
|View full text |Cite
|
Sign up to set email alerts
|

The Faintest Wise Debris Disks: Enhanced Methods for Detection and Verification

Abstract: In an earlier study, we reported nearly 100 previously unknown dusty debris disks around Hipparcos mainsequence stars within 75 pc by selecting stars with excesses in individual WISE colors. Here, we further scrutinize the Hipparcos75 pc sample to (1) gain sensitivity to previously undetected, fainter mid-IR excesses and (2) remove spurious excesses contaminated by previously unidentified blended sources. We improve on our previous method by adopting a more accurate measure of the confidence threshold for exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Surveys carried out by space-based observatories such as Spitzer, Herschel, and WISE have uncovered hundreds of stars within ∼200 pc with a significant infrared excess in their spectral energy distributions at 22-24μm suggesting the presence of warm circumstellar dust (e.g., Trilling et al 2008;Carpenter et al 2009;Cotten & Song 2016;Patel et al 2017;Silverberg et al 2018), or a colder component identified by an excess at 70-160 μm (e.g., Hillenbrand et al 2008;Matthews et al 2010;Eiroa et al 2013;Sibthorpe et al 2018). The identification of these circumstellar disks has also coincided with several high-contrast imaging surveys targeting stars with an infrared excess (e.g., Janson et al 2013;Rameau et al 2013;Nielsen et al 2019;Launhardt et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys carried out by space-based observatories such as Spitzer, Herschel, and WISE have uncovered hundreds of stars within ∼200 pc with a significant infrared excess in their spectral energy distributions at 22-24μm suggesting the presence of warm circumstellar dust (e.g., Trilling et al 2008;Carpenter et al 2009;Cotten & Song 2016;Patel et al 2017;Silverberg et al 2018), or a colder component identified by an excess at 70-160 μm (e.g., Hillenbrand et al 2008;Matthews et al 2010;Eiroa et al 2013;Sibthorpe et al 2018). The identification of these circumstellar disks has also coincided with several high-contrast imaging surveys targeting stars with an infrared excess (e.g., Janson et al 2013;Rameau et al 2013;Nielsen et al 2019;Launhardt et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys carried out by space-based observatories such as Spitzer, Herschel and WISE have uncovered hundreds of stars within ∼200 pc with a significant infrared excess in their spectral energy distributions at 22-24 µm suggesting the presence of warm circumstellar dust (e.g. Trilling et al 2008;Carpenter et al 2009;Cotten & Song 2016;Patel et al 2017;Silverberg et al 2018), or a colder component identified by an excess at 70-160 µm (e.g. Hillenbrand et al 2008;Matthews et al 2010;Eiroa et al 2013;Sibthorpe et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They are composed of kilometersized planetesimals formed during the earlier protoplanetary stage of the system, and of dust particles generated by colliding bodies through a destructive grinding cascade stirred by secular perturbations from planets or large planetesimals (see Wyatt 2008 for a review). About 500 debris disk systems have been identified around nearby stars from their photometric excess in the infrared (Eiroa et al 2013;Chen et al 2014;Patel et al 2017), revealing that massive dust systems are as common as 20% to 26% around A to K type stars in the solar neighborhood (Thureau et al 2014;Montesinos et al 2016).…”
Section: Introductionmentioning
confidence: 99%